Characteristics and working conditions of moonlighting teachers: Evidence from the 2011-2012 Schools and Staffing Survey - Paul G Fitchett; Tina L Heafner; Susan Harden (Arizona State University, 2016)
Educational research has long established moonlighting as a popular employment practice among public school teachers. Using data from the National Center for Education Statistics Schools and Staffing Survey, this study examined both the characteristics and motivations of public school teachers across moonlighting categories. Findings indicate that teacher characteristics, workplace perceptions, and professional outlook varied across moonlighting type. The likelihood of moonlighting outside of the education sector increased among single, male teachers with high reported burnout and lower salaries. Results have implications for how school leaders and policymakers should view moonlighting inside and outside the education sector.